Festuca coelestis Increases Drought Tolerance and Nitrogen Use via Nutrient Supply–Demand Relationship on the Qinghai-Tibet Plateau - Ningning Zhao; Xingrong Sun; Shuai Hou; Sujie Ma; Guohao Chen; Zelin Chen; Xiangtao Wang; Zhixin Zhang (Plants, 2023)
Drought and nutrient deficiency pose great challenges to the successful establishment of native plants on the Qinghai-Tibet Plateau. The dominant factors and strategies that affect the adaptation of alpine herbs to dry and nutrient-deficient environments remain unclear. Three water gradients were established using two-factor controlled experiments: low water (WL), medium water (WM), and high water (WH). The field water-holding capacities were 35%, 55%, and 75%, respectively. Nitrogen fertilizer (N) was applied at four levels: control (CK), low (FL), medium (FM), and high (FH) at 0, 110, 330, and 540 mg/kg, respectively. The results revealed that N was the main limiting factor, rather than phosphorous (P), in Festuca coelestis under drought stress. Under water shortage conditions, F. coelestis accumulated more proline and non-structural carbohydrates, especially in the aboveground parts of the leaves and stems; however, the root diameter and aboveground nitrogen use efficiency were reduced. Appropriate N addition could mitigate the adverse effects by increasing the release of N, P, and enzyme activity in the bulk soil and rhizosphere to balance their ratio, and was mainly transferred to the aboveground parts, which optimized the supply uptake relationship. The effects of water and fertilizer on the physiological adaptability and nutrient utilization of F. coelestis were verified using structural equation modeling. Based on their different sensitivities to water and nitrogen, the WHFM treatment was more suitable for F. coelestis establishment. Our results demonstrated that the disproportionate nutrient supply ability and preferential supply aboveground compared to below ground were the main factors influencing F. coelestis seedling establishment under drought conditions. This study provides evidence for a better understanding of herbaceous plants living in high mountain regions and offers important information for reducing the risk of ecological restoration failure in similar alpine regions.